2020
DOI: 10.1186/s12909-020-1970-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress, stressors and related factors in clinical learning of midwifery students in Iran: a cross sectional study

Abstract: Background: Midwifery is an emotionally challenging profession, and academic education of midwifery especially clinical learning has its own specific challenges. Midwifery students face with stressful experiences, especially related to instructor and characteristics of clinical environment, which can affect their theoretical and practical abilities. There is insufficient evidence in this field. This study aimed to explore (1) the perceived stress and stressors of midwifery students and (2) the relationships be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
0
21
0
2
Order By: Relevance
“…Previous studies showed that students of nursing and midwifery are frequently exposed to significantly high levels of stress during clinical practice (Blomberg et al, 2014;Labrague et al, 2017;Pryjmachuk & Richards, 2008;Shaban et al, 2012). The students' sources of stress connected with clinical practice include: taking care of patients, professional training, professional communication and time management (Soares de Souza et al, 2016), dying patients and patients with terminal illnesses (Zhao et al, 2015), fear of unknown situations, dealing with unfamiliar situations, making errors with patients, learning to apply clinical procedures and managing technical instruments (Pulido-Martos et al, 2012), noise, moving location, social interaction (Ahmed & Mohammed, 2019), unpleasant emotions, humiliating experiences, feeling suffering due to seeing for patients with critical situation (Rezaei et al, 2020), difficult relationships with clinical colleagues and clinical educators (Wolf et al, 2015). In Brazilian studies, nursing students complained about problems related to the lack of time for: leisure activities, spending time with family members and for completion of extracurricular activities (Soares de Souza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that students of nursing and midwifery are frequently exposed to significantly high levels of stress during clinical practice (Blomberg et al, 2014;Labrague et al, 2017;Pryjmachuk & Richards, 2008;Shaban et al, 2012). The students' sources of stress connected with clinical practice include: taking care of patients, professional training, professional communication and time management (Soares de Souza et al, 2016), dying patients and patients with terminal illnesses (Zhao et al, 2015), fear of unknown situations, dealing with unfamiliar situations, making errors with patients, learning to apply clinical procedures and managing technical instruments (Pulido-Martos et al, 2012), noise, moving location, social interaction (Ahmed & Mohammed, 2019), unpleasant emotions, humiliating experiences, feeling suffering due to seeing for patients with critical situation (Rezaei et al, 2020), difficult relationships with clinical colleagues and clinical educators (Wolf et al, 2015). In Brazilian studies, nursing students complained about problems related to the lack of time for: leisure activities, spending time with family members and for completion of extracurricular activities (Soares de Souza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This research is in line with the results of research conducted by Rosyad (2019) where most (59.3%) the stress level of students who are writing their thesis is in the normal category, 18.5% mild stress, 11.1% moderate stress, 7.4% severe stress, and 3.7% very severe stress. The other study by Rezaei, Falahati and Beheshtizadeh (2020) with 70 participants shows that approximately 56% of the midwifery students perceived a high level of stress. In addition, a study by Aulia and Panjaitan (2019) on students of the Faculty of Nursing, Universitas Indonesia who are currently completing their thesis, showed that 77 respondents (71.3%) experienced moderate stress, 15 respondents (13.9%) experienced mild stress, and 16 respondents (14.8%) experienced severe stress.…”
Section: Discussionmentioning
confidence: 86%
“…27 studies [16–42] were included, including 7116 patients. The results of meta-analysis showed that the prevalence rate of low-level stress was 0.24% [95% CI (0.24% to 0.25%)], the prevalence rate of medium level stress was 0.35% [95% CI (0.35% to 0.35%)], and the prevalence rate of high-level stress was 0.10% [95% CI (0.10% to 0.10%)], as shown in Figures 3–5.…”
Section: Resultsmentioning
confidence: 99%
“…There were 17 high stress level studies. [17][18][19][20][21][22][23][24][25][26]28,30,32,34,36,41,42] respectively. Chi square test showed that the differences between the subgroups were statistically significant (P < 0.00001).…”
Section: Prevalence Of Stress Level In Different Survey Timementioning
confidence: 99%